Interpretation of Change in Stress Measurement using Strain Gauge during Stressing of Pre-stressing Cables in a Bridge Span - Partha Pratim Roy, Amitava Sil (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper presents a comprehensive study of the interpretation of changes in stress measurements using strain gauges during stressing of prestressed cables in a bridge span. The use of prestressed concrete in bridge construction has become prevalent owing to its ability to counteract tensile stresses and enhance structural integrity. Strain gauges are commonly employed to monitor the stress levels within the prestressing cables during the stressing process. This paper employs computer simulations to analyze and interpret the changes in stress measurements obtained from strain gauges during cable stressing, contributing to a deeper understanding of the structural behavior and load distribution. The study employs a finite element analysis (FEA) to simulate the cable stressing process, providing insights into the stress redistribution within the bridge span. The findings highlight the significance of accurate stress interpretation in ensuring the safety and efficiency of pre-stressed concrete bridge structures.